Five decades of scientific publications in Social Work about clinical and experimental research - Sarasola Fernández, Alberto; Barrera-Algarín, Evaristo; Caravaca-Sánchez, Francisco; Sarasola Sánchez-Serrano , José Luis (IJERI: International Journal of Educational Research and Innovation, 2021)
This article analyzes how Social Work has been able to connect professional practice with the generation of knowledge. Social Work has the capacity to generate scientific knowledge directly from its professional intervention, and specifically, through the evaluation of its professional intervention. For this, Social Work has used different scientific methodologies and procedures for decades and have consolidated its generation of scientific knowledge. In this case we refer to the use of experimental and quasi-experimental designs, and the so-called Single Case Evaluation Designs (SCDE). Their diverse types and potentialities for the direct generation of scientific knowledge from the evaluation of professional practice are described. Method: We analyze the level of publications about experimentation and SCDE using Scopus Database, working with data exported from 1960 to the present. And estructurated by 14 variables. Findings: There is a significant increase in the number of publications about “Experiment in Social Work’ and ‘Single-Case Evaluation Designs in Social Work’, especially in the last decade. The United States and United Kingdom are the largest producer of experimentation in Social Work. Applications: We conclude that Social Work has been able to use these methodological research strategies to consolidate its capacity for research and generation of knowledge, both for the generation of theory and for professional intervention.